Real Options and Conventional NPV in PT Telkom's ODP Establishment Capital Budgeting Issues - Indah Sari, Dely; Budi Nugroho, Anggoro (The Indonesian Journal of Business Administration, 2017)
Abstract. Telkom has had a desire for the establish of ODP thorough in areas that allow to do the establish of the ODP is not limited to areas and regions of both the city center area and the area of peripheral or entire region Bandung and outside the city of Bandung, but that is not possible because of the lack of funding that Telkom owned so in the end must choose an area that it can be built ODP that can provide benefits to Telkom and which areas can not be built ODP because less beneficial for Telkom. Telkom in making the decision to establish the ODP in an area is to see if the area is feasible or not feasible. if an area is declared feasible to establish ODP then Telkom will invest in the area. Conversely if the area is declared not feasible then Telkom will not invest in these area. The establish project ODP include the type of project undertaken by Telkom is mutually exclusive project means when Telkom chose to do the establish of ODP in the city center area will eliminate the chance of the project more are in the area peripherals, it should be an option (the election) in the second the area so that management can make decisions which areas can be used for the establish of ODP and areas that can not be done ODP establish.Keywords: Optical Distribution Point (ODP) city center area (ANI), peripheral area (Cipatat), mutually exclusive project.